OTX2 restricts entry to the mouse germline. (25th October 2018) - Zhang, Jingchao; Zhang, Man; Acampora, Dario; Vojtek, Matúš; Yuan, Detian; Simeone, Antonio; Chambers, Ian
Abstract The successful segregation of germ cells from somatic lineages is vital for sexual reproduction and species survival. In the mouse, primordial germ cells (PGCs), precursors of all germ cells, are induced from the post-implantation epiblast1 . Induction requires BMP4 signalling to prospective PGCs2 and the intrinsic action of PGC transcription factors3–6 . However, the molecular mechanisms that connect BMP4 to induction of the PGC transcription factors that are responsible for segregating PGCs from somatic lineages are unknown. Here we show that the transcription factor OTX2 is a key regulator of these processes. Downregulation ofOtx2 precedes the initiation of the PGC programme both in vitro and in vivo. Deletion ofOtx2 in vitro markedly increases the efficiency of PGC-like cell differentiation and prolongs the period of PGC competence. In the absence ofOtx2 activity, differentiation of PGC-like cells becomes independent of the otherwise essential cytokine signals, with germline entry initiating even in the absence of the PGC transcription factor BLIMP1. Deletion ofOtx2 in vivo increases PGC numbers. These data demonstrate that OTX2 functions repressively upstream of PGC transcription factors, acting as a roadblock to limit entry of epiblast cells to the germline to a small window in space and time, thereby ensuring correct numerical segregation of germline cells from the soma. The transcription factor OTX2 ensures that germline induction is initially kept in check and only proceeds after OTX2 downregulation.